Meta-analyses in Economic Psychology: A sustainable approach to cross-cultural differences - Matteo M. Marini; Giulia Ulivieri (Masaryk University, Faculty of Economics and Administration, 2024)
This manuscript is a methodological work on the state of research using meta-analytic procedures in Economic Psychology, with a focus on the investigation of cross-cultural differences. We review published meta-analyses and introduce a new classification thereof by data source, describing how the different categories relate to the study of cross-cultural differences. We also discuss related opportunities and challenges, proposing a sustainable methodological approach that is then implemented in three case studies where we re-analyze data from published meta-analyses. In doing so, the relevance of culture as a determinant is explored by relating country-level cultural indicators to experimental measures of risk aversion, tax compliance, and prosocial behavior, respectively. It turns out that, after we control for country-level cultural heterogeneity and economic development, country-level individualism predicts these economic outcomes. We discuss possible interpretations of our findings.
Keywords: C90; Z10; 330; meta-analysis; individualism; fractionalization; Multiple Price List; Tax Evasion Game; Dictator Game